Prevalence and Profile of Central Serous Chorioretinopathy in an Indian Cohort - Sahoo, Niroj Kumar; Singh, Sumit Randhir; Kammari, Priyanka; Jonnadula, Ganesh Babu; Das, Anthony Vipin; Chhablani, Jay (Nepalese Journal of Ophthalmology, 2019)
Aims: To determine the profile of CSCR patients from a tertiary health care set-up in India. Methods and Material: A total of 2780 (2447 males and 333 females) patients with a diagnosis of CSCR were included. Data regarding the demographics, profile of CSCR and systemic diseases, if any, were collected from a tertiary eye care network in South India from January 2012 to December 2016. Results: The prevalence of CSCR was found to be 1.7% (A total 2780 patients, with mean age of 42.3±10.1 years). A total of 2031 patients had a unilateral and 749 had bilateral involvement. Acute and chronic CSCR was seen in 1932 (69.5%) and 848 (30.5%) eyes respectively. The mean uncorrected visual acuity of the patients was 0.51±0.45 log MAR (Snellen equivalent 20/60) while the mean best corrected visual acuity was 0.32±0.40 log MAR (Snellen equivalent 20/40). History of smoking and steroid use was present in 214 (7.7%) and 758 (27.3%) individuals respectively. Hypertension and diabetes mellitus was present in 106 (3.8%) and 51 (1.8%) patients respectively. Most of patients 824 (29.6%) patients were shift-workers. Laser was done in 336 (12.1%) acute and 223 (8%) chronic CSCR patients. Photodynamic therapy was used in 12 acute and 12 chronic cases. Conclusion: Prevalence of CSCR was 1.7%. The study provides an overview of patient profile among Indian subjects.